Analisis Ekspresi P53 pada Karsinoma Urotelial Kandung Kemih Derajat Rendah dan Derajat Tinggi serta Hubungannya dengan Stadium Tumor - Kusmardi; Imelda Setiana Silitonga; Budiana Tanurahardja (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2021)
BackgroundUrothelial carcinoma is the most common bladder malignancy in men. Risk factors include smoking, chemicals exposure, radiation,schistosoma hematobium infection. P53 mutation is the most common mutation in urothelial bladder carcinoma that cause p53 proteinaccumulation which are detected through immunohistochemical examination. The aim of this study is to analyze the differencesbetween p53 expression in low and high grade urothelial and the carcinomas association of p53 expression with tumor stage.MethodsThis was a cross sectional study with 47 cases (22 cases of low grade and 25 cases of high grade) urothelial carcinoma in AnatomicalPathology Department Faculty Medicine of Universitas Indonesia/Cipto Mangunkusumo Hospital (FKUI/RSCM) in 2009-2017. Allcases stained with p53 antibody with immunohistochemical methods with positive cut off ≥20%.ResultsP53 positive expression are found in 33 samples, 20 cases of high grade and 13 cases in low grade; 22 cases of Nonmuscle invasivebladder cancer and 11 cases of Muscle invasive bladder cancer.ConclusionThe expression of p53 in low grade and high grade urotelial carcinoma of the bladder and its association with tumor stage showed nosignificant difference.